Factors Affecting Government Agency Performance Moderated by Organizational Commitment - Suharyati, Suharyati; Taufik, Taufeni; Nurulita, Suci (Indonesian Journal of Economics, Social, and Humanities, 2025)
This study aims to determine the factors that affect the performance of government agencies, such as good governance, organizational culture, and leadership style moderated by organizational commitment. This study consisted of 43 populations, the entire of OPD in Riau Province, and used the purposive sampling technique to determine the sample size to obtain 30 research sample. Data collection in this study used a questionnaire given to 90 respondents, including the head of the finance subdivision, the head of the planning and program subdivision, and the head of the general and staffing subdivision. Then, the analysis is carried out using Warp PS 7.0. The results of this study concluded that good governance, organizational culture, and leadership style affect the performance of government agencies, and organizational commitment is able to moderate the effect of good governance and leadership style on the performance of government agencies. However, organizational commitment is not able to moderate the effect of organizational culture on the performance of government agencies, meaning that good or bad organizational commitment is not a determinant in increasing or decreasing the effect of organizational culture on the performance of government agencies.